ASPEK-ASPEK MATEMATIKA PADA ATRIBUT YANG DIGUNAKAN DALAM TRADISI TEMU MANTEN DI MADIUN - Dian, Mariani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
Ethnomathematics could be viewed as an effort to look back at how mathematics integrated in culture and life. Ethnomathematics appears to rectify the perception that mathematics has nothing to do with everyday life. This perception, directly or indirectly influences students’ understanding of mathematical concepts and alsi influences students’ interest in learning and developing these concepts. This study aims to examine the mathematical aspects contained in the attributes used in Temu Manten Tradition, especially the tradition carried out in Madiun City. In this article, the research is limited to only a few attributes used in Temu Manten. Ethnographic approach is  used in this research. The results of subsequent research were processed qualitatively, so that it was concluded that the attributes used in this tradition, with deeper exploration could be associated with mathematical concepts, specifically on geometrical aspects such as plane, including transformation,  perimeter or circumferences and area of the plane , solid geometry, congruency of triangles,  rotating object, volumes of rotating objects,  the rotary axis and the constant volume.